Efektivitas Relaksasi Progresif dalam Mengurangi Gejala Depresi Pasien Diabetes Melitus Tipe 2 - Hotma Rumahorbo; Nani Avianti; Desmaniarti Zaini (Politeknik Kesehatan Tanjung Karang, 2018)
The prevalence of Diabetes Mellitus (DM) in Indonesia shows an increase from 1.1% in 2007 to 2.1% in 2013, with the most cases being Type 2 Diabetes Mellitus. DM is a chronic disease that cannot be cured but can be controlled by healthy lifestyle and medicine. DM patients who cannot control their blood sugar levels, they will experience acute and chronic complications such as diabetic retinopathy, diabetic nephropathy, and diabetic neuropathy, causing the patient to undergo hospital treatment for the management of blood sugar levels and complaints arising from the accompanying illness. This situation makes the patient stress and depression which will aggravate the disease. This study was to measure the effectiveness of progressive relaxation interventions on depressive symptoms of DMT-2 patients. The study design used Quasi-Experimental two groups pre and post-test design, with 61 samples consisting of 31 intervention groups and 30 control groups. The intervention group was given guidance and progressive relaxation exercises 2 times a day for 3 consecutive days with a duration of 30 minutes each exercise. The results showed that progressive relaxation interventions in DMT-2 patients reduced depression scores by -11,368 units significantly (p=0.001). Variable that makes it difficult to reduce depression symptoms were blood glucose levels. Blood glucose levels were increasing depression scores by 0.012 units. The conclusion was a progressive relaxation intervention effectively reduce depression scores of DMT-2 patients. Controlling the patient's blood glucose levels is important in improving the effectiveness of progressive relaxation interventions to reduce depressive symptoms of DMT-2 patients.